(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to explore the implementation of loose parts media in early childhood education contexts in Indonesia. The identified problem is the dominance of conventional learning media that limits children’s exploration and creativity. The research employed a qualitative approach with library research design, involving interpretative analysis of 15 selected literature sources from 2014-2024. Findings revealed three implementation typologies: curriculum- integrated model, exploration zones, and project-based approaches; as well as the effectiveness of loose parts media in stimulating children’s cognitive, socio- emotional, physical-motor development, and creativity. Implementation challenges are multidimensional, including teachers’ paradigmatic resistance and curricular integration difficulties. Successful strategies require an ecosystemic approach that harmonizes transformations in materials, pedagogical practices, and institutional philosophical orientations, aligned with the 21st-century competency development vision in the Merdeka Curriculum.